Cardiometabolic Health and Longitudinal Progression of White Matter Hyperintensity: The Mayo Clinic Study of Aging. Issue 11 (November 2019) - Scharf, Eugene L.; Graff-Radford, Jonathan; Przybelski, Scott A.; Lesnick, Timothy G.; Mielke, Michelle M.; Knopman, David S.; Preboske, Gregory M.; Schwarz, Christopher G.; Senjem, Matthew L.; Gunter, Jeffrey L.; Machulda, Mary; Kantarci, Kejal; et al.
Abstract : Background and Purpose—: White matter hyperintensity (WMH) burden is associated with stroke and cognitive decline. Risk factors associated with the longitudinal progression of WMH in the general population have not been systematically investigated. To investigate the primary midlife and current cardiometabolic risk factors associated with changes in WMH over time in a population cohort. Methods—: This cohort study included participants enrolled in the Mayo Clinic Study of Aging, a longitudinal population-based study in Olmsted County, Minnesota with at least 2 consecutive WMH assessments on fluid-attenuated inversion recovery-magnetic resonance images (n=554, ≥60 years with midlife assessments) with relevant baseline laboratory measures of interest. Linear mixed model regression was used to determine the important components of cardiometabolic risk profile at baseline that were associated with future progression of WMH. These analyses were controlled for age and sex. Sensitivity analyses were conducted using stratification by sex. The main outcome measure was percent change in WMH normalized to total intracranial volume. Three sets of models were constructed to evaluate individual (1) midlife risk factors, (2) current risk factors including the presence of metabolic syndrome and its constituents, and (3) baseline measurements of continuous laboratory measures of cardiometabolic risk. Results—: Age was the strongest predictor of progression in WMH ( P <0.001). Baseline hypertension ( P <0.001), midlife hypertension ( P =0.003), and baseline fasting glucose in males ( P =0.01) were predictive of WMH change. The presence of metabolic syndrome was not associated with progressive WMH. In sensitivity analyses, associations between hypertension and WMH progression were stronger in females. Baseline serum glucose was associated with increase in WMH but was not significant in females in the stratified analysis. Other continuous laboratory measures of vascular risk were not associated with progressive WMH. Conclusions—: Midlife and current hypertension in all participants and fasting glucose in males were associated with quantitative changes in white matter. Prospective clinical studies should determine optimal blood pressure to reduce stroke and cognitive impairment during aging. Abstract : Supplemental Digital Content is available in the text.